Radiation dose to circumscribed brain regions and neurocognitive function in patients with meningioma. Issue 3 (19th February 2022) - Sekely, Angela; Tsang, Derek S; Mabbott, Donald; Kongkham, Paul; Zadeh, Gelareh; Zakzanis, Konstantine K; Edelstein, Kim
Abstract: Background: Although radiation (RT) is standard treatment for many brain tumors, it may contribute to neurocognitive decline. The objective of this study was to investigate associations between RT dose to circumscribed brain regions and specific neurocognitive domains in patients with meningioma. Methods: We undertook a retrospective study of 40 patients with meningioma who received RT and underwent an in-depth clinical neurocognitive assessment. Radiation dosimetry characteristics were delineated based on treatment planning computerized tomography co-registered with contrast-enhanced 3D T1-weighted magnetic resonance imaging. Principal components analysis was applied to organize neurocognitive test scores into factors, and multivariate multiple linear regression models were undertaken to examine if RT dose to circumscribed brain regions is associated with specific neurocognitive outcomes. Results: Radiation dose to brain regions was associated with neurocognitive functions across a number of domains. High dose to the parietal-occipital region was associated with slower visuomotor processing speed (mean dose, β = −1.100, P = .017; dose to 50% of the region [D50], β = −0.697, P = .049). In contrast, high dose to the dorsal frontal region was associated with faster visuomotor processing speed (mean dose, β = 0.001, P = .036). Conclusions: These findings suggest that RT delivered to brain regions (ie, parietal-occipital areas) may contribute to poor neurocognitive outcomes. Given that modern radiotherapy techniques allow for precise targeting of dose delivered to brain regions, prospective trials examining relations between dose and neurocognitive functions are warranted to confirm these preliminary results.